Abuse potential of 2-(4-iodo-2, 5-dimethoxyphenyl)N-(2-methoxybenzyl)ethanamine (25INBOMe); in vivo and ex vivo approaches. (May 2019) - Jeon, Seo Young; Kim, Young-Hoon; Kim, Sung Jin; Suh, Soo Kyung; Cha, Hye Jin
Abstract: 25INBOMe ("25-I", "N-Bomb"), one of new psychoactive substances (NPSs), is being abused for recreational purpose. However, the liability for abuse or dependence has not been systematically studied yet. The objective of the present study was to evaluate rewarding and reinforcing effects of 25INBOMe using conditioned place preference (CPP) and self-administration (SA) paradigms. In addition, ultrasonic vocalizations (USVs) were measured to investigate relationships between USVs and emotional state regarding dependence on psychoactive substances. To understand molecular mechanism involved in its action, dopamine (DA) level changes were analyzed using synaptosomes extracted from the striatal region of the brain. Expression level changes of SGK1 (serum/glucocorticoid regulated kinase 1) and PER2 (period circadian protein homolog 2), two putative biomarkers for drug dependence, were also analyzed. Results showed that 25INBOMe increased both CPP (0.3 mg/kg) and SA (0.03 mg/kg/infusion) and produced higher frequencies in USVs analysis. It also increased DA levels in the striatal region and changed expression levels of SGK1 and PER2. Results of the present study suggest that 25INBOMe might produce rewarding and reinforcing effects, indicating its dependence liability. In addition, frequencies of USV might be associated with emotional state of mice induced by psychoactive substances regarding substance dependence. This is the first systemic preclinical report on the dependence liability of 25INBOMe and the first attempt to introduce a possible relationship between USVs and emotional state of mice regarding substance dependency. Further studies are needed to clarify the mechanism involved in 25INBOMe dependency and determine the usefulness of USV measurement as a method for evaluating dependence liability. Highlights: 25INBOMe might produce rewarding and reinforcing effects, indicating its dependence liability. The dependence liability of 25INBOMe would be related with dopaminergic pathway in the brain. Frequencies of ultrasonic vocalization (USV) might be associated with substance dependence.